Towards yeast fermentation monitoring: Enhanced sensing performance with nanostructured platinum integrated microsensors array - Nurul Izni Rusli; Ruben Van den Eeckhoudt; Catarina Fernandes; Filippo Franceschini; Dimitrios Konstantinidis; Kevin J. Verstrepen; Frederik Ceyssens; Michael Kraft; Irene Taurino (Sensing and Bio-Sensing Research)
Effective and continuous monitoring of bioprocesses requires the parallel screening of multiple key parameters to enhance the processes and ultimately improve the quality of the end products. In this work, the development and characterization of only few square millimeters microfabricated multi-sensor array chip for analysis of yeast fermentation is described. We originally integrated platinum nanostructures (nano-Pt) on the microelectrodes by a simple, CMOS compatible, and scalable electrodeposition procedure. This step was proven to be pivotal to obtain highly sensitive and selective microsensors with minimal cross-talk and measurement variability. Nano-Pt enables reliable sensing at lower applied potentials, offering a promising solution to mitigate electrical cross-talk in closely integrated sensor configurations. The multi-sensor features potentiometric parallel-plate nanostructured electrodes for measuring pH, interdigitated nano-Pt electrodes for indirectly measuring microbial growth and activity by measuring the electrolyte conductivity, and microelectrodes based on nano-Pt for measuring dissolved oxygen (DO) and glucose via amperometry. Importantly, all-solid-state on-chip reference electrodes for potentiometric and amperometric sensors of this chip have been developed and characterized to enable standalone measurements and achieve true miniaturization, avoiding the need for external conventional reference electrodes. The chip includes a meander thin-film resistance temperature detector for temperature monitoring as well. Our platform represents the first step towards viable in-situ monitoring of lab-scale yeast fermentation and to control the homogeneity of process parameters in large scale bioreactors.